Influence of the surface moraine on the state of Djankuat Glacier (Central Caucasus) by 2025 - A. A. Rezepkin; V. V. Popovnin (Лëд и снег, 2018)
Current glaciation of the Central Caucasus is in the regressive stage of evolution. Observed long rising of the air temperature in the ablation seasons (almost 1 °C since 1968 on the Djankuat Glacier) together with insignificant growth of winter precipitation caused a long period of the glacier degradation: since 1871 the mass balance of the glacier, with rare exceptions, remained negative. During this time, the glacier has lost about 60 m w.e. mainly by areas of the smallest ice thickness, i.e. the steep slopes of the rocky framing of the fi n basin which become exposing from ice due to conditions of extreme instability. In parallel with the processes of freezing and thawing in cracks, this leads to a signifi ant increase in the frequency of rockfalls. In 2001–2003, huge rockfalls occurred on the glacier from the slopes, which had recently undergone deglaciation. The last one covered 4% of the glacier surface with about 70 000 m3 of clastic products. The marine cover differs significantly from the open ice surface in its thermal characteristics, which affect the structure of the thermal balance and the absolute values of ablation. The temperature inside the moraine is positive throughout the ablation season, even at a depth of 60 cm, but the absolute values of daily maximum melting are five times lower than those on open ice. The influence of the moraine material layer on the ablation is determined not only by its thickness, but also by the structure. The fi ld experiment conducted in 2011 demonstrated that melting under a layer of coarse-grained material (particle diameter 16–17 cm) is four times faster than under a layer of fi e-grained (7–8 cm) material equal in thickness. The study of the influence of the surface moraine and the account of its further growth in thickness and area made it possible to predict changes in the surface of the glacier by 2025. The climatic forecast was made using the HadCM3 model (A2 climate change scenario). Data on air temperature and precipitation were used to construct a predictive fi ld of the mass balance of the Djankuat Glacier for each year until 2025. Th s became possible by the use of a quantitative parameterized relationship between the mass balance of the entire glacier and each of its points, identifi d in the study of the total mass transfer of the glacier, as well as parameterized linear regression equations. The forecast of hypsometry of the Djankuat Glacier made it possible to determine that by 2025 the depression of the tongue areas covered by the moraine will be 7–15 m (or 42–45%) smaller than areas of the open ice. Th s means that at the present stage of the glaciation development the surface moraine plays a role in the evolution of the glacier, commensurable with the climate factor.